2009
DOI: 10.4137/cmc.s730
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myocardial Scar; Comparison between 18F-FDG PET, CMR and 99Tc-Sestamibi

Abstract: Objective: Patients with heart failure and ischaemic heart disease may obtain benefit from revascularisation if viable dysfunctional myocardium is present. Such patients have an increased operative risk, so it is important to ensure that viability is correctly identified. In this study, we have compared the utility of 3 imaging modalities to detect myocardial scar.Design: Prospective, descriptive study. Setting: Tertiary cardiac centre.Patients: 35 patients (29 male, average age 70 years) with coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…First, when comparing SPECT to CMR, while there was no significant difference in each method's ability to detect myocardial transmural necrosis or normal myocardium, LGE CMR was superior to SPECT in the detection of subendocardial infarction owing to its superior spatial resolution. 97) 98) 99) In addition, a recent prospective study has shown that CMR has a sensitivity of 86.5% and a specificity of 83.4% in the detection of CAD, which are superior to the 66.5% sensitivity and 82.6% specificity reported for SPECT. 13) Likewise, CMR appears to be superior to dobutamine stress echocardiography, which is known to have a similar overall accuracy to that of SPECT on the basis of a meta-analysis that compiled 11 studies and reported a sensitivity of 79% and specificity of 87%.…”
Section: Contentsmentioning
confidence: 99%
“…First, when comparing SPECT to CMR, while there was no significant difference in each method's ability to detect myocardial transmural necrosis or normal myocardium, LGE CMR was superior to SPECT in the detection of subendocardial infarction owing to its superior spatial resolution. 97) 98) 99) In addition, a recent prospective study has shown that CMR has a sensitivity of 86.5% and a specificity of 83.4% in the detection of CAD, which are superior to the 66.5% sensitivity and 82.6% specificity reported for SPECT. 13) Likewise, CMR appears to be superior to dobutamine stress echocardiography, which is known to have a similar overall accuracy to that of SPECT on the basis of a meta-analysis that compiled 11 studies and reported a sensitivity of 79% and specificity of 87%.…”
Section: Contentsmentioning
confidence: 99%
“…Late gadolinium enhancement CMR was also compared to other noninvasive tests for myocardial viability, such as dobutamine stress echocardiography and SPECT. First, when comparing SPECT to CMR, while there was no significant difference in each method's ability to detect myocardial transmural necrosis or normal myocardium, LGE CMR was superior to SPECT in the detection of subendocardial infarction owing to its superior spatial resolution ( 97 , 98 , 99 ). In addition, a recent prospective study has shown that CMR has a sensitivity of 86.5% and a specificity of 83.4% in the detection of CAD, which are superior to the 66.5% sensitivity and 82.6% specificity reported for SPECT ( 13 ).…”
Section: Contentsmentioning
confidence: 99%
“…Despite 201 Tl, 99m Tc‐based radiopharmaceuticals have a worse relationship to flow and minimal redistributing properties, and the mitochondrial uptake of these compounds requires an intact mitochondrial membrane and oxidative metabolism, thus the basis for sensitive viability detection [100]. Recent study compared the detection of viable myocardium by 18 F‐FDG, MRI and 99m Tc‐sestamibi (MIBI) and demonstrated that a significantly higher number of segments were identified as scar by MIBI than by either 18 F‐FDG or CMR [101]. However, the greatest discrepancy between MIBI and 18 F‐FDG and MRI was in detection of scar of the inferior and lateral wall.…”
Section: Imaging Of Self‐renewed Myocardiummentioning
confidence: 99%